Blockchain in manufacturing revolution based on machine to machine transaction: a systematic review - Martins, Geraldo Dolce; Gonçalves, Rodrigo Franco; Petroni, Benedito Cristiano (Brazilian Journal of Operations & Production Management, 2019)
In the last few years, two technological events emerged. First, the rising of Industry 4.0 concepts and technologies such as IoT allowed the direct link between machines on the shop floor, establishing a machine-to-machine communication (M2M). Second, blockchain enables transactions such payments and contracts without a formal reliable or accreditation institutions, such as banks or government. Goal: The goal of this paper is to explore the state-of-art of the blockchain technology applied to the manufacture sector. In this sense, the option of the M2M transaction being intermediated by blockchain on the shop floor is a hypothesis to be tested. Moreover, it could be questioned if these subjects are being appreciated by the academia. Design / Methodology / Approach: a systematic review of the literature was conducted, considering blockchain, the industrial context, and the Industry 4.0 related technologies. Results: As a result, only 12 papers that were classified according to their application fields and practice stages were obtained. Limitations of the investigation: this field of application is brand new; thus, the available literature is scarce; only 12 papers were obtained. Practical implications: As the main result, it was identified that the possibilities of blockchain applications to Industry have been poorly explored by literature. Originality / Value: The paper addresses the possibility of application of blockchain in M2M-based manufacture, and detaches the research gap in the academic literature related to it.